Becoming the World Versus Identity Politics - Bal, Mieke (Nordlit, 2009)
Taking up some moments from the documentary film Becoming Vera, in this article I offer a plea for a cultural life "de-limited" by identity (Schimanski and Wolfe). Through the awaking cultural awareness of a three-year-old girl who negotiates borders established by education, linguistics, gender, and nationality, mostly by ignoring their relevance, I speculate that too exclusive or tenacious a focus on cultural, ethnic, racial, and other identities erects more boundaries than it levels. Secondarily, I contend that a messy mixture of identities not only enhances but in fact constitutes the vibrancy of cultural life. The film also shows the unavoidable framing of individuals - in this case, the framing of a child - that occurs simultaneously to their negotiation of borders.